2021
DOI: 10.1002/aqc.3486
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the complex habitat use of the white mullet, Mugil curema, in several coastal environments from Neotropical Pacific and Atlantic waters

Abstract: The white mullet, Mugil curema, is a widely distributed euryhaline species, the migratory behaviour of which is poorly understood. The objective of this work was to study the large‐scale habitat use of this species for the first time. Several environments were considered, such as euryhaline and hypersaline lagoons, the sea, and a river, distributed in the Central Pacific (Mexico) and Atlantic (Gulf of Mexico, Caribbean Sea‐Venezuela, and north‐eastern Brazil). Otolith core‐to‐edge Sr/Ca ratios of 163 fish, det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…Diversity in migration behavior has been documented in many fish species, such as Mugil spp. (Chang et al 2004b, Avigliano et al 2021a), Coilia spp. (Yang et al 2006, Jiang et al 2019, and sticklebacks Gasteroteus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Diversity in migration behavior has been documented in many fish species, such as Mugil spp. (Chang et al 2004b, Avigliano et al 2021a), Coilia spp. (Yang et al 2006, Jiang et al 2019, and sticklebacks Gasteroteus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Sr/Ca changes were more stable in OW juvenile. Avigliano et al (2021) indicated that in species inhabiting salinities of 20-35%, the Sr/Ca ratio had a limited ability to discriminate movement between habitats. Nevertheless, some individuals will experience a period of higher salinity habitats in the early developmental stage.…”
Section: Analysis Of the Life History Of A Latus With Different Body ...mentioning
confidence: 99%